Potential Analysis and Development of Reservoir Water for Ecotourism at Gajah Mungkur Wonogiri. (April 2018) - Muryani, C; Santoso, S; Utomowati, R
Abstract: Gajah Mungkur Dams in Wonogiri Regency has been developed into a tourism area but the tourism industry is less developed. This research aimed to 1) analyze the potential and the barriers ecotourism development of reservoir water, 2) analyze the direction of developing reservoir water ecotourism. Data collections were through field observation, laboratory analysis of water and interviews. Data analysis for the potential and barriers of the water reservoir ecotourism was done using qualitative descriptive, while for the direction of reservoir water ecotourism development was done using SWOT analysis. The result showed 1) The reservoir water at Gajah Mungkur Dams was very potential as ecotourism for touring around the dams, organic keramba, water park and traditional attraction; the barriers of the water reservoir ecotourism development are reservoir retreading, the water quality and environment sanitation; 2) The result of SWOT analysis for the development of water reservoir for ecotourism were to maximize the strength; increase opportunities and eliminate weaknesses.